NBS/DBU mediated one-pot synthesis of α-acyloxyketones from benzylic secondary alcohols and carboxylic acids. Issue 46 (9th November 2016) - Zhu, Minghui; Wei, Wei; Yang, Daoshan; Cui, Hong; Cui, Huanhuan; Sun, Xuejun; Wang, Hua
Abstract : A simple and efficient NBS/DBU-mediated one-pot procedure has been developed for the synthesis of α-acyloxyketones from benzylic secondary alcohols and carboxylic acids. Abstract : A simple and efficient one-pot NBS/DBU-mediated method has been developed for the synthesis of α-acyloxyketones from various benzylic secondary alcohols and carboxylic acids. Through this methodology, a series of α-acyloxyketones could be obtained in good to excellent yields under mild conditions. Importantly, this new reaction avoids the direct usage of toxic metal catalysts or potentially dangerous peroxide oxidants.